2020
DOI: 10.1101/2020.09.23.20200030
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological characterization of symptomatic and asymptomatic COVID-19 cases and positivity in subsequent RT-PCR tests in the United Arab Emirates

Abstract: Background The COVID-19 RT-PCR confirmed cases could be symptomatic or asymptomatic. In the United Arab Emirates (UAE), the identified COVID-19 RT-PCR confirmed cases are yet to be characterized. In this study, we characterized the first cohort of COVID-19 RT-PCR confirmed cases reported in the Abu Dhabi Emirate, UAE, according to symptomatic state, and identified factors associated with the symptomatic state. Also, the strength of association between the symptomatic state and testing positive in three subsequ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…In line with our findings, infectivity may be weaker in asymptomatic elders than in those fully developing symptoms 22 . A recent study showed similar results in PCR retesting in SARS-CoV-2 asymptomatic and symptomatic patients, and interestingly, this could be evidenced during the first week after diagnosis 23 .…”
Section: Discussionsupporting
confidence: 60%
“…In line with our findings, infectivity may be weaker in asymptomatic elders than in those fully developing symptoms 22 . A recent study showed similar results in PCR retesting in SARS-CoV-2 asymptomatic and symptomatic patients, and interestingly, this could be evidenced during the first week after diagnosis 23 .…”
Section: Discussionsupporting
confidence: 60%
“…Rapid antigen testing has shown great promise for symptomatic patients; however, the sensitivity in asymptomatic and presymptomatic subjects reaches only ~ 73% [ 12 ]. Asymptomatic individuals are those who test RT-qPCR positive but experience no COVID-19 symptoms, they occur at a rate of 17–20% [ 3 , 4 , 18 ], with a higher prevalence in younger subjects [ 2 ]. Presymptomatic individuals are those who initially present as asymptomatic and develop symptoms days or weeks later [ 3 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the United Arab Emirates (UAE), the first PCR-confirmed case of COVID-19 was reported on 29 January, 2020 (7). Since then, all efforts were put into understanding the disease characteristics, with massive testing, contact tracing, nonpharmaceutical interventions, new therapeutic modalities, and vaccination; all playing a crucial role in containing the spread of COVID-19 infection in the UAE (7). In Abu Dhabi, the capital and the largest city in the UAE, 43% of the first diagnosed cohort of the COVID-19-confirmed cases were asymptomatic (7).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, all efforts were put into understanding the disease characteristics, with massive testing, contact tracing, nonpharmaceutical interventions, new therapeutic modalities, and vaccination; all playing a crucial role in containing the spread of COVID-19 infection in the UAE (7). In Abu Dhabi, the capital and the largest city in the UAE, 43% of the first diagnosed cohort of the COVID-19-confirmed cases were asymptomatic (7). Although reports demonstrated that COVID-19 infection is less severe in children compared to adultsit includes mainly mild or moderate infections (2,(4)(5)(6))yet, severe illness due to COVID-19 can occur in children, requiring hospitalization and intensive care (8).…”
Section: Introductionmentioning
confidence: 99%